Fermentation Method with the Help of Extremely Low Frequency (ELF) Magnetic Field Radiation to Support Luwak Coffee Superior Products in Sidomulyo Village, Silo District, Jember Regency, East Java - Sudarti Sudarti; Singgih Bektiarso; Alex Harijanto; Yushardi Yushardi; Trapsilo Prihandono; Sumardi Sumardi (Pascasarjana Universitas Mataram, 2022)
Coffee production in Sidomulyo Village, located at the foot of Mount Gumitir, Silo District, Jember Regency, is famous for being very abundant. This condition is very supportive of the increasing needs of coffee drink lovers. However, the taste of ready-to-brewed ground coffee produced by the Sidomulyo Koperasi WANITA is still unable to compete with coffee on the market. This activity aimed to provide training on civet coffee production through the dry coffee bean fermentation method as a primary ingredient. The fermentation process was carried out using a Magnetic Fermentation machine which was the result of research in 2020. The fermentation process training activity was attended by 15 members of the Koperasi WANITA. 50 kg of dry coffee was fermented using a Magnetic Fermenter machine. Dry coffee was soaked first in warm water (temperature around 30 - 400C) for 5 hours. Then it was drained and put in a fermenter box by adjusting the intensity of the ELF magnetic field to around 300 T for 90 minutes. The coffee beans were transferred to buckets and ripened for up to 5 days, then washed and sun-dried for three days, after drying in Roasting and continue grinding. The targeted outputs of this activity included scientific publications in the National Journal of Abdimas with ISSN. The results of this activity had produced fermented coffee beans that had been roasted in the form of roasted coffee beans and ground coffee. Based on the results of the evaluation, the members of the Ketakasi Koperasi already had skills in producing artificial Luwak coffee. This had the potential to develop superior products for Sidomulyo civet coffee.